CIPP Model Evaluation of Research Learning Program at MTsN 2 Kota Kediri - Munawaroh, Diah Ambarumi; Nur Salim (JEET, Journal of English Education and Technology, 2022)
This evaluation aims to evaluate the implementation and progress of the research learning activity program achieved by students at MTsN 2 Kota Kediri for the 2019/2020 school year. The Madrasah Tsanawiyah educational institution cannot be separated from several obstacles. Based on the information obtained, the implementation of research learning activities has not been maximized, such as infrastructure is inadequate, responsibility, and student discipline is still lacking. The evaluators see the many benefits and obstacles of implementing this program activity so that they can provide suggestions or input in the future. This evaluation uses the CIPP evaluation model on the Context, Input, Processes, and Product aspects. Carry out four-month activities from August 23 - to December 18, 2020. The results of this evaluation are (1) Evaluation Context legality of research learning based on the Decree of the Director-General of Islamic Education Number 6757 of 2020 concerning the designation of madrasas as research providers in Indonesia. (2) Input Evaluation, The main madrasah facilities are quite adequate. Unless the human resources component is inadequate, it is necessary to add additional teaching staff. (3) Evaluation Processes, which consist of lesson planning, learning implementation, learning assessment, and project documents, have gone well and according to the criteria. (4)EvaluationThe results follow the criteria for evaluating the value of research learning above the KKM and are categorized as good. In terms of management, MTsN 2 Kota Kediri already has an activity program plan and a good priority scale to implement the activity program. An organizational structure and job descriptions have been prepared, and an evaluation of scheduled activities.